2019
DOI: 10.1093/jbcr/irz128
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Securing Dermal Substitutes and Skin Grafts to Difficult Portions of the Face Using a Custom 3D-Printed Facemask

Abstract: Management of third-degree facial burns remains one of the most difficult challenges in burn care. Patients with deep facial burns usually require gradual escharectomy, tangential excision of the wound, and resurfacing with full-thickness skin grafts or dermal substitutes associated with split-thickness skin grafts to provide better and superior cosmetic results. Immobilization of skin grafts and dermal substitutes by reducing shearing forces and hematoma formation underneath is paramount to improve success ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Wei et al also demonstrated the applicability of aforementioned approach in pediatric population [ 13 ]. In addition to HS prevention, Aguilar et al described the use of personilized 3D-printed facemask for securing dermal substitute and skin graft [ 14 ]. Patient’s face was scanned using portable 3D scanner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wei et al also demonstrated the applicability of aforementioned approach in pediatric population [ 13 ]. In addition to HS prevention, Aguilar et al described the use of personilized 3D-printed facemask for securing dermal substitute and skin graft [ 14 ]. Patient’s face was scanned using portable 3D scanner.…”
Section: Discussionmentioning
confidence: 99%
“…Existing literature examined the use of 3D printed facial orthosis using rigid material [ 12 14 ]. However, in this pilot case study, in addition to rigid PLA-facemask, 3D-printed TPU-facemask was also assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Broader applications in reconstructive microsurgery include identifying ideal perforator vessels with computed tomography angiograms and using these same patient images in VR/AR as an operative guide during flap harvest 20–22 . More specialized uses for 3D printing include the creation of customized face masks to support full-thickness skin grafts over concave areas of the face after third-degree facial burns, to minimize tension and shear forces of these grafts during recovery, and promote optimal healing 23 . Bioprinting, a burgeoning field in tissue engineering that focuses on printing tissue scaffolds and various cell types, also holds great promise for 3D printed tissues but is beyond the scope of this review.…”
Section: Narrowing the Gap Between Concept And Realitymentioning
confidence: 99%